Perception Towards Tabloidization: A Case of B-Metro Tabloid in Zimbabwe - Ndlovu, Mandla (Journal of Humanities and Social Sciences Studies, 2020)
This paper explores the perceptions of audiences towards the B-metro tabloid in Bulawayo, the second largest city of Zimbabwe. The paper reports the results of a qualitative research that was undertaken to examine different ways in which people receive the tabloid at audience level. The sample was drawn from various sections of population in the community of Bulawayo. Groups such as church members, parents, the employed, unemployed as well as students were included in the study. The inclusion of these groups was necessitated by the fact that different sections of audiences are affected by media content in different ways. Data was collected using the interviews and focus group discussions. The research revealed that the reception of B-metro tabloid varies from individual to individual. It came out that the social status of individuals shapes their perceptions of the tabloid. The church members view B-metro in a different way from the non-Christians. School children have their own perceptions of the tabloid which are different from their parents. Complaints were also raised against the content of the tabloid. Some members of the community tend to shun it. There is a general feeling among members of the society that stories covered are not true or are over-exaggerated by the tabloid. The paper also points out that tabloid journalism is questionable among the Bulawayo audience. The research recommended that B-metro must incorporate community development ideas in its content. This will reduce its trivialization by part of audience and attract more readers who currently read serious news in mainstream media only. Awareness campaigns be conducted such that people are taught about the differences between mainstream media mandate versus the mandate of the tabloid in a society.